PTU-108 Uptake and clinical outcomes of self-referred bowel-scope (flexible sigmoidoscopy) screening appointments at ST mark's hospital. (8th June 2018) - Kerrison, Robert; Prentice, Andrew; Marshall, Sarah; Wagner, Christian von; Ruwende, Jo
Abstract : Background: As part of the 2017 Commissioning for Quality and Innovation (CQUIN) scheme, NHS England commissioned St Mark's Hospital to send its bowel-scope (flexible sigmoidoscopy) screening non-responders a self-referral reminder on the first anniversary of their initial invitation. The aim of this analysis was to examine uptake and clinical outcomes for the CQUIN during the first six months of implementation. Methods: We used data from an on-going study monitoring self-referred appointments at St Mark's Hospital in London. Uptake and clinical outcomes were assessed using descriptive statistics. Differences in uptake between men and women were examined using univariable logistic regression. The data were analysed in SPSS (v25.0). Results: Between April and October 2017, 4281 men (n=2000, 46.7%) and women (n=2281, 53.3%) were sent a self-referral reminder on the anniversary of their initial invitation. The overall uptake was 6.2% (n=267), and was higher among women than men (uptake was 7.1% and 5.5%, respectively; Odds Ratio: 1.32, 95% Confidence Intervals: 1.03–1.69). Thirty (12.5%) of those who self-referred for screening had adenomas detected. Fifteen were subsequently referred for colonoscopy. Discussion: The implementation of a 12 month self-referral reminder at St Mark's Hospital led to a substantial number of additional men and women being screened, as well as the detection of several high-risk adenomas. Future refinements to the process would include additional reminders at 24, 36 and 48 months, as well as four week follow-up reminders within each self-referral episode. Evidence from the present analysis suggests that the interventions could reduce existing inequalities in uptake between men and women